Identification of Bird Species at the University of Pattimura - La Eddy; Restu Tuharea; Mechiavel Moniharapon (Universitas Syiah Kuala, 2020)
Birds are very dynamic so they can live in all areas including on campus. The purpose of this study was to identify the types of birds that exist on the University of Pattimura campus. Retrieval of data using MacKinnon 10 species of birds. The results showed that at Pattimura University Campus 26 species of birds were found. This shows that the Pattimura University campus is a location to find food for several species of birds. The results of this study also showed that in each faculty different types of birds were found.